Ein Kopf des Darius am ehemaligen Postfuhramt in Berlin - von Gall, Hubertus (Anabasis. Studia Classica et Orientalia, 2010)
The article is dealing with the reception of Achaemenid art and history in modern European art. Starting point is a relief medaillon with the representation of Darius, son of Hystaspes (522–486 B.C.), which is part of the sculptural decoration of the Postfuhramt (postal carriage office) in Berlin, erected about 1881. The sculpture is placed at the beginning of 25 relief portraits of famous discoverers, explorers and scientists, which have intensively promoted traffic and communication by their work from the earliest times until the that-time present period. The choice of Darius I. at the beginning of a series of historical personages is unique and unprecedented in European art of the 19 th century and after and needs a specific explanation. Since in regard to the other personages represented political and military achievements can be ruled out, one has to look for a motivation in the field of culture and communication. In a representation in the General Post Office in Berlin, which was about ten years older than the Postfuhramt but is, unfortunately, no longer existing, the contributions of the different peoples to the development of the post were shown in 12 paintings. The fourth of these figured two Persian horsemen in the act of passing a message from one to the other. This was evidently an allegorical rendering of the courier system carried out on the royal roads and described by Herodotus 8.98. This ’effectively earliest postal system in the world’ (M. Brosius) was evidently the reason for placing the Persians, personified by Darius, son of Hystaspes, at the beginning of an ancestral gallery of the men who promoted the progress of post and communication through the ages. Consequently the artist, in relying partly on a reconstruction proposal of Charles Texier (1852) and partly on Assyrian reliefs from Khorsabad put considerable efforts into the representation of the Persian Great King Darius I. as exactly as this was possible in his time.